Debora Dan Kepemimpinan Perempuan Dalam Konteks Indonesia - Taneo, Rolin Ferdilianto Sandelgus (DIEGESIS: Jurnal Teologi Kharismatika, 2024)
Women are not actually second class citizens in society.  Women can actually lead too.  However, public awareness of choosing women is still low.  Moreover, in the Indonesian political calendar, in 2024 Indonesia will elect leaders both above the executive and legislative branches.  This article is intended to find out the causes of women’s minimal involvement in the Indonesian political arena.  After that, this article will also show the role of women in leading.  This context will be put into dialogue with the story of Deborah in the Bible, who was also a successful female leader.  The result of this dialogue is to provide a leadership perspective that is not gender biased.  The building in this paper uses the literature method, namely by looking at literature that specifically discusses the two topics that are currently in the spotlight, namely the role of Deborah and the contribution of Indonesian women in leading. Keywords: Deborah; women; leadersAbstrakPerempuan sesungguhnya bukan warga kelas dua dalam masyarakat. Perempuan juga sebenarnya bisa memimpin. Hanya saja, kesadaran publik untuk memilih perempuan masih rendah. Apalagi dalam kalender politik Indonesia, tahun 2024 ini Indonesia akan memilih pemimpin baik di atas eksekutif maupun legislatif. Adanya tulisan ini dimaksudkan untuk mencari tahu penyebab keterlibatan perempuan yang minim di arena politik Indonesia. Setelah itu, tulisan ini juga akan menampilkan tentang bagaimana peran perempuan dalam memimpin. Konteks ini akan didialogkan  dengan kisah Debora dalam Alkitab yang juga adalah pemimpin perempuan yang berhasil. Hasil dialog ini yakni memberi suatu perspektif kepemimpinan yang tidak bias gender. Bangunan dalam tulisan ini menggunakan metode kepustakaan yaitu dengan melihat literatur-literatur yang secara khusus membahas kedua topik yang sementara menjadi sorotannya yaitu peran Debora dan kontribusi perempuan Indonesia dalam memimpin.Kata Kunci: Debora; perempuan; pemimpin